HAK ASUH ANAK DALAM PERSPEKTIF KHI DAN MADZHAB SYAFI’I - Ahmad Baidawi; Muhammad Zainuddin Sunarto (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
In principle, the responsibility of caring for children is the burden of both parents, whether they are still living in harmony or a divorce has occurred. Hadanah itself is an act that must be carried out against their parents, because without Hadanah it will result in the child being neglected and his life is wasted, because if the child is still small or not yet mumayyiz, it is very well nurtured and educated, and will have a negative impact on their future. , can even challenge the existence of their soul. Child care, in the view of KHI, includes all the needs that can support the development of the child's life both in the scope of primary and secondary needs, such as the need for education, living expenses, peace of life, welfare, especially in health.In Shafi'i's view regarding child custody (hadanah), children who are seven years old are allowed to choose for themselves if both parents are equally worthy to take care of their hadhanah, be it in matters of religion, property or affection. so the child is invited to choose it, on the grounds that the child is considered to be able to distinguish which one is good and what is bad for himself, therefore the child is given the freedom to choose what he thinks the child is able to make his own choice whether to follow his mother or follow his father .